2018
DOI: 10.1002/aur.1937
|View full text |Cite
|
Sign up to set email alerts
|

Proneness to guilt, shame, and pride in children with Autism Spectrum Disorders and neurotypical children

Abstract: This research examined proneness to guilt, shame, and pride in children with Autism Spectrum Disorders (ASD) and neurotypical children. We found that children with ASD showed less proneness to guilt than neurotypical children. Better understanding of theory of mind was related to greater proneness to guilt and pride, but only for children with ASD. These findings are important because these complex emotions are linked with both positive and negative social behaviors towards others and oneself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
(73 reference statements)
2
14
1
1
Order By: Relevance
“…Among these studies, two have examined the relations between ToM and moral emotions. They found that ToM abilities were positively related to self-reported levels of guilt (Davidson et al, 2018) and to the recognition of shame and embarrassment in children with ASD (Heerey et al, 2003).…”
Section: Moral Emotions In Children With Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these studies, two have examined the relations between ToM and moral emotions. They found that ToM abilities were positively related to self-reported levels of guilt (Davidson et al, 2018) and to the recognition of shame and embarrassment in children with ASD (Heerey et al, 2003).…”
Section: Moral Emotions In Children With Asdmentioning
confidence: 99%
“…Overall, studies reported lower levels of moral emotions especially shame and guiltin children with ASD. Children with ASD aged 7-15 reported themselves to experience less shame and guilt than non-ASD peers (Davidson et al, 2018;Novin et al, 2019). When describing their personal experience of shame and guilt, children with ASD aged 8-13 provided accounts that were less personalized and less contextually appropriate (Losh & Capps, 2006).…”
Section: Moral Emotions In Children With Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by more recent research showing that while people with ASD are quite competent in dealing with basic emotions, such as joy and grief, they struggle with more complex emotions, such as pride and shame (Davidson et al . 2018). The results of the current study may provide an explanation for this observation, as emotions such as ‘pride’ and ‘shame’ are acquired later in the course of ED (Capps et al .…”
Section: Discussionmentioning
confidence: 99%
“…A person who experiences difficulties in attributing mental states to others will show a reduced propensity to experience self-conscious emotions and, therefore, might be less likely to comply with societal norms. Indeed, numerous studies have shown that people with ASD experience self-conscious emotions less frequently than neurotypical people (e.g., Capps et al 1992;Davidson et al 2018;Losh and Capps 2006). Arguably, if autistic people tend to feel fewer self-conscious emotions, they may be less affected by what other people think about their cross-gender behaviour and therefore less likely to feel pressure to conform of gender norms.…”
Section: Discussionmentioning
confidence: 99%